CAREER AND ITS DEVELOPMENT IN THE ORGANIZATION (Research Bulletins of the Faculty of Economic Sciences, 2021)
One of the most important factors in competing countries in the economic climate is the quality of the workforce, among other things determined by obtaining employ-ment. Career path for professional development is aimed precisely to gain employment.For some, it is associated with well-paid and interesting work, for others, while putting more and more new goals and achieve success through career progression.This article aims to show the essence of their careers and their possible courses of both women and men.
Keywords: career, career development, career management